Transition to Sharia-Compliant Finance in Aceh: Miscommunication, Misperceptions, and Resistance - Bayumi, Muhamad Rahman; Jaya, Rizal Alfit; Diem, M. Junestrada (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
The implementation of Qanun (Islamic Law) Aceh No. 11 of 2018, mandating all financial institutions in the province of Aceh, Indonesia, to operate solely on Islamic principles from January 4, 2022, sparked protests from certain parties, and thus became a nationwide controversy. Some media reports often depicted the Qanun as causing heightened unemployment and poverty due to the exclusion of conventional banking. This research investigates the discourse contestation surrounding the prohibition of conventional banks in Aceh. Employing a philosophical qualitative approach, the study analyzes instances of miscommunication, misperceptions, and resistance concerning the Qanun's implementation. Primary data collection involved interviews with diverse stakeholders, including grassroots communities, members of the Sharia Economic Society (MES), the Indonesian Association of Islamic Economists (IAEI), Financial Services Authority (OJK) officials, religious leaders, and economists. Researcher observations conducted in 2019 and 2022 in Aceh further enriched the data. Secondary data, comprising online news and relevant documents, supplemented the findings. Through triangulation techniques and an integration-interconnection paradigm, the study revealed that the perceived conflict was largely amplified by media portrayals of protests, often lacking comprehensive and objective analysis. Consequently, this study proposes solutions, strategies, and models to facilitate the effective implementation of the Qanun, aiming to realize its intended benefits and contribute to Aceh's sustainable progress through the advancement of maqashid sharia.========================================================================================================ABSTRAK – Transisi ke Keuangan Syariah di Aceh: Miskomunikasi, Mispersepsi, dan Resistensi. Qanun Aceh No. 11 Tahun 2018, yang mewajibkan penerapan prinsip keuangan syariah di seluruh lembaga keuangan di Aceh sejak 4 Januari 2022, memicu berbagai reaksi dan menjadi perbincangan nasional. Media massa kerap mengaitkan Qanun ini dengan peningkatan angka pengangguran dan kemiskinan di Aceh akibat pelarangan operasional perbankan konvensional. Penelitian ini mengkaji kontestasi wacana terkait pelarangan bank konvensional di Aceh menggunakan pendekatan kualitatif filosofis. Penelitian ini menganalisis miskomunikasi, mispersepsi, dan resistensi terkait penerapan Qanun Aceh No. 11 Tahun 2018. Data primer dikumpulkan melalui wawancara dengan berbagai pemangku kepentingan, termasuk komunitas akar rumput, anggota Masyarakat Ekonomi Syariah (MES), Ikatan Ahli Ekonomi Islam (IAEI), pejabat Otoritas Jasa Keuangan (OJK), tokoh agama, dan ekonom. Observasi lapangan juga dilakukan pada tahun 2019 dan 2022. Data sekunder berupa berita online dan dokumen relevan lainnya turut dikaji untuk memperkaya analisis. Teknik triangulasi dan paradigma integrasi-interkoneksi digunakan untuk menganalisis data. Analisis menunjukkan bahwa resistensi terhadap Qanun tersebut sebagian besar disebabkan oleh penggambaran media tanpa analisis yang komprehensif dan objektif, seringkali hanya fokus pada satu atau dua kejadian. Penelitian ini menawarkan beberapa solusi, strategi, dan model untuk memfasilitasi penerapan Qanun yang efektif dan mencapai manfaat yang diinginkan, serta berkontribusi pada kemajuan Aceh yang berkelanjutan melalui pemajuan maqashid syariah.